Pengaruh Kualitas Pelayanan dan Variasi Produk Terhadap Minat Beli Pada Warkop Kampoeng Pisang Kota Palopo - Nadya Putri; Irawati Irawati; Yones Yones; Munawir Munawir (Movere Journal, 2025)
Coffee shops are an integral part of the lifestyle of modern society, especially among young people. Along with the proliferation of warkops, consumers are increasingly selective in choosing a place to socialize and enjoy coffee. They pay attention not only to the atmosphere, but also to the quality of service and variety of products offered. Therefore, this study aims to find out (1) the impact of service quality on consumer buying interest, (2) the impact of product variations on consumer buying interest and (3) the impact of service quality and product variety on consumer buying interest in Warkop Kampoeng Pisang, Kota Palopo. The data collection techniques used in this study were observation, questionnaire, and interview. These three techniques are used by researchers because seeing a phenomenon that occurs will be better if they use observation techniques, making questionnaires, and interviews. By using a multiple analysis test of research results conducted by 30 respondents on customers of Warkop Kampoeng Pisang, Kota Palopo. The results of the study show that simultaneously, the quality of service and product variety have a significant influence on consumer buying interest. However, partially, the results of the t-test showed that the quality of service did not have a significant influence on consumer buying interest, while product variety had a significant influence on consumer buying interest. This implies that at Warkop Kampoeng Pisang, Kota Palopo, product variety is a more dominant factor in influencing consumer buying interest compared to service quality.